Penerapan Model Pembelajaran Aktif dengan Media Pencocokan Kartu Indeks untuk Meningkatkan Hasil Belajar Riset Keperawatan pada Mahasiswa - Sugeng Riyadi; Ruti Wiyati; Welas Haryati (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2015)
The goal of the research is to improve student learning outcomes in the use of active learning model with index cards matching. We use pre–postttest Quasy method without control group. The Data were analyzed by using paired t test. Based on the analysis of the data, the level of student’s knowledge increases prior to the application of the active learning method with index card matching method. Index cards matching method can improve student participation, achievement, and motivation.